Effects of urban particulate matter on the quality of erythrocytes. (February 2023) - Tian, Yaxian; Li, Yuxuan; Sun, Sujing; Dong, Yanrong; Tian, Zhaoju; Zhan, Linsheng; Wang, Xiaohui
Abstract: With the acceleration of industrialisation and urbanisation, air pollution has become a serious global concern as a hazard to human health, with urban particulate matter (UPM) accounting for the largest share. UPM can rapidly pass into and persist within systemic circulation. However, few studies exist on whether UPM may have any impact on blood components. In this study, UPM standards (SRM1648a) were used to assess the influence of UPM on erythrocyte quality in terms of oxidative and metabolic damage as well as phagocytosis by macrophages in vitro and clearance in vivo. Our results showed that UPM had weak haemolytic properties. It can oxidise haemoglobin and influence the oxygen-carrying function, redox balance, and metabolism of erythrocytes. UPM increases the content of reactive oxygen species (ROS) and decreases antioxidant function according to the data of malonaldehyde (MDA), glutathione (GSH), and glucose 6 phosphate dehydrogenase (G6PDH). UPM can adhere to or be internalised by erythrocytes at higher concentrations, which can alter their morphology. Superoxide radicals produced in the co-incubation system further disrupted the structure of red blood cell membranes, thereby lowering the resistance to the hypotonic solution, as reflected by the osmotic fragility test. Moreover, UPM leads to an increase in phosphatidylserine exposure in erythrocytes and subsequent clearance by the mononuclear phagocytic system in vivo. Altogether, this study suggests that the primary function of erythrocytes may be affected by UPM, providing a warning for erythrocyte quality in severely polluted areas. For critically ill patients, transfusion of erythrocytes with lesions in morphology and function will have serious clinical consequences, suggesting that potential risks should be considered during blood donation screening. The current work expands the scope of blood safety studies. Graphical abstract: Image 1 Highlights: This work focuses on the health effects of UPM on blood safety. UPM influences the oxygen-carrying function and osmotic fragility of erythrocytes. Morphological changes were due to metabolic impairments and oxidative damage. UPM-damaged erythrocytes readily cleared by mononuclear phagocytic system in vivo .